ANALISIS PERTUMBUHAN DAN DAYA SAING EKONOMI DI KABUPATEN INDRAGIRI HULU - Eka Sry W Binventy; Djaimi Bakce; Susy Edwina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The analysis of economic growth and competitiveness of the region is very important to formulate the planning of the region’s growth. This study aims to analyze the growth and competitiveness of the economy in Indragiri Hulu. The purpose of this study used secondary data, the Central Department of Statistics of Riau Province and the Central Department of Statistics of Indragiri Hulu in 2008 and 2012 were analyzed by the method of shift share. This study concluded that there are some districts that have high growth and high competitiveness. They are, District Peranap, District Batang Peranap, District Lirik, District Seberida, District Sungai Lala, District Lubuk Batu Jaya, District Rengat, District Pasir Penyu, and District Rengat Barat. The recommendation of this study is the required to observe the potential and the advantages of each district to improve the management and the utilization of the wealth of natural resource and the effectiveness of efficiency. The most important aspects of the development district in Indragiri Hulu are the development and the improvement of infrastructure, the potential of agricultural development, and increase of  the additional cost of agricultural products. Keywords: Economic Growth, Competitiveness, Shift Share